Teachers’ beliefs on the benefit of collaboration in lesson study - Khalid, Madihah; Abdullah, Nor Azura; Kamoludeen, Abdulhameed (International Islamic University Malaysia., 2016)
Lesson study is being actively implemented in many countries as one of the continuous professional development programs for school teachers. Since collaboration is an important element of lesson study, it is deemed necessary to investigate teachers’ beliefs about collaboration in lesson study. Data were collected through both qualitative and quantitative methods, where teachers were surveyed via questionnaire, interviewed, observed and asked to keep a journal. Thirty-one teachers and a school administrator were involved. The results showed that most teachers agree with the benefits of lesson study, espeially that it improved cooperation and collegiality. Other benefits include: lesson study provides a platform for sharing collaboratively; knowledge is enhanced in terms of content, pedagogy, student-centered instructions , and curricula – ability to design constructivist lessons. Negative comments were centered around time constraints and heavy workload – leading to absence from shceduled meetings. Overall, the effect of collaboration in lesson study has led to more improved teachers compared to other professional development approaches.